2016
DOI: 10.1007/s00380-016-0913-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum microRNA-21 levels with Visfatin, inflammation, and acute coronary syndromes

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that regulate gene expression. It seems that microRNA-21 (miR-21) and Visfatin, a novel adipocytokine, play roles in inflammation and atherosclerosis. The aim of this study was to investigate the association of miR-21 with Visfatin, inflammation, atherosclerosis and acute coronary syndrome (ACS). Based on coronary angiography and electrocardiogram (ECG), 53 patients with ACS and 52 patients with stable CAD were enrolled in this study. We assayed serum miR-21, Visfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Additionally, expression of miR-21 levels was also positively correlated with MMP-9, high sensitivity C-reactive protein, and aging. e present study also found that C-reactive protein and history of coronary artery disease were significantly higher in stable and unstable angina patients than controls [26].…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, expression of miR-21 levels was also positively correlated with MMP-9, high sensitivity C-reactive protein, and aging. e present study also found that C-reactive protein and history of coronary artery disease were significantly higher in stable and unstable angina patients than controls [26].…”
Section: Discussionsupporting
confidence: 76%
“…For example, the decreased miR-145 expression was demonstrated to serve as a prognostic biomarker in the patients with gastric cancer [31]. Plasma miR-145 expression was determined as a diagnostic biomarker for the differentiation of cervical cancer cases from healthy individuals [32]. Given the decreased expression of miR-145 in ACS patients, we investigated its diagnostic value using the ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…But whether miR-21 plays pro or anti-inflammation role still remains conflicting. By using microarray, the expression of miR-21 was found to be elevated in human advanced coronary atherosclerotic plaques and serum from acute coronary syndrome patients, respectively [43,44].…”
Section: Discussionmentioning
confidence: 99%